Prejudice toward Islamic fundamentalists: The role of social domination orientation and interreligious empathy among Christian students in Surabaya - The, Aurelia Theresa Nagata; Tondok, Marselius Sampe (University of Muhammadiyah Malang, 2023)
Interreligious conflicts can change the state system regarding religious tolerance and the emergence of terrorist behavior. In Surabaya, terrorism incidents have occurred in three Christian churches, and the alleged perpetrators are the Islamic fundamentalist group JAD. These incidents have fueled feelings of threat and fear of death, which can lead to prejudice. This research aimed to determine the role of social dominance orientation and interreligious empathy as predictors of prejudice toward Islamic fundamentalists. It used a quantitative design with a sample of 400 Christian students aged 17-24 in Surabaya. Furthermore, SDO-7, BES-A, and the Prejudice toward Islamic Fundamentalists Scales were adopted. The results showed that social dominance orientation and interreligious empathy predicted the prejudice toward Islamic fundamentalists (R=0.056; R2=0,061; F(2, 378)=12.876; p<0.001) using multiple linear regression tests. Social dominance orientation did not significantly predict prejudice (t= -0.91426; p=0.361), unlike interreligious empathy (t=4.365; p<0.001). Therefore, intergroup relations need to consider interreligious empathy in reducing prejudice.